The Effects of I-bLA on Resolving the Issues of the EFL Students’ Writing Skills and Content Originality - Telaumbanua, Yohannes; Martini, Martini; Aulia, Dhini; Djonnaidi, Silvia (Jurnal Pendidikan Progresif, 2021)
The Effects of I-bLA on Resolving the Issues of the EFL Students’ Writing Skills and Content Originality. Objective: This research aims at testing the effects of Inquiry-based Learning Approach (I-bLA) on Resolving the Issues of the EFL Students’ Writing Skills and Content Originality. Method: The one Group Pre-test and Post-test experimental research design was used to test the effects of I-bLA. Findings: The result of paired sample test explicates that the sig. 2-tailed value is 0.000 designating a significant difference between pre-test and post-test. Furthermore, the I-bLA significantly decreases the similarity index by 80% meaning that the content originality of the students’ essays does not match against the original sources. Conclusion: the use of I-bLA can significantly resolve the issues of the EFL students’ Writing Skills and Content Originality. Keywords: I-bLA, writing skills, content originality DOI: http://dx.doi.org/10.23960/jpp.v11.i2.202106